Translation procedures applied in English – Vietnamese translation of macroeconomic terminologies = Phương thức dịch được áp dụng trong dịch Anh – Việt các thuật ngữ kinh tế học vĩ mô - Nguyễn, Tuấn Minh (2021)
Economic knowledge in general and macroeconomic knowledge in particular has become popular and so the translation of the terminologies in these fields. This paper tries to research the translation procedures applied in English – Vietnamese translation of macroeconomic terms in the 5th and 7th editions of the book called “Macroeconomics” by N.Gregory Mankiw basing on the translation theory of Newmark. This paper hopes to point out what procedures are applied and what is the most dominating one. First, this study provides some theoretical review of translation and translation procedures to function as the basis for the study. The translation procedures proposed by Newmark (1988) have been chosen for the analysis of application. Applying qualitative and quantitative for 252 terms selected, the researcher finds out that 11 translation procedures are utilized. They are literal translation, naturalization, through translation, transposition, synonym, recognized translation, componential analysis, paraphrase, transference, modulation, and couplets. The most dominating procedure is through translation. Although there remain some limitations, the researcher hopes that this paper will be useful for students and translators in dealing with macroeconomic terms.